Agroecology - McCune, Nils; Rosset, Peter [UNESP] (My University, 2021)
Agroecology is the systematization of the Indigenous knowledge systems that have produced food for millennia; since the 1980s, it has emerged as a fusion of science, practice, and a movement for global change. To the degree that agroecology has gained prominence as an approach toward food system sustainability, transnational corporations and public institutions vie with social movements to define agroecology and its potential. As a collective praxis of food sovereignty, agroecology is becoming a globally relevant tool for land and class struggle in the hands of rural communities and popular movements.